2006
DOI: 10.1176/ajp.2006.163.9.1569
|View full text |Cite
|
Sign up to set email alerts
|

Job Performance Deficits Due to Depression

Abstract: Objective-This study assessed the relationship between depression severity and job performance among employed primary care patients.Method-In a 2001-2004 longitudinal observational study of depression's affect on work productivity, 286 patients with DSM-IV major depressive disorder and/or dysthymia were compared to 93 individuals with rheumatoid arthritis, a condition associated with work disability, and 193 depression-free healthy control subjects. Participants were employed at least 15 hours per week, did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
224
2
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(244 citation statements)
references
References 34 publications
11
224
2
7
Order By: Relevance
“…One potential explanation may be that due to the high variability in the duration until partial/full RTW, our power was insufficient to detect significant differences between treatment groups. Second, as previous studies have indicated that functional improvement lags behind symptom reduction,32 it is possible that our follow-up period of 18 months was too short for measuring whether additional effects in depression recovery lead to further improvement in work outcomes after the 18-month follow-up. Finally, an important factor that may have contributed to the discrepancy in study findings is the rapid societal changes that have occurred in The Netherlands since our previous study.…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation may be that due to the high variability in the duration until partial/full RTW, our power was insufficient to detect significant differences between treatment groups. Second, as previous studies have indicated that functional improvement lags behind symptom reduction,32 it is possible that our follow-up period of 18 months was too short for measuring whether additional effects in depression recovery lead to further improvement in work outcomes after the 18-month follow-up. Finally, an important factor that may have contributed to the discrepancy in study findings is the rapid societal changes that have occurred in The Netherlands since our previous study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to human costs, economic costs have to be taken into account too: people lose 5.6 hours of productive work every week when they are depressed (5): it has been estimated how half of the loss of work productivity is due to absenteeism and short-term disability (6,7). People with symptoms of depression are 2.17 times more likely to take sick days (8) and, when they are at work, their productivity is impaired, depending on how severe the depression is. Workplace costs of depression have been estimated being over $34 billion per year (9); as the costs of absenteeism were directly related to actually taking antidepressant medications (10), those people who took the prescribed medication had a 20% lower cost of absenteeism.…”
Section: Introductionmentioning
confidence: 99%
“…Z innej strony zaobserwowano, że nawet niewielkie nasilenie objawów negatywnie wpływa na produktywność pracowników [43].…”
Section: Nr 1 64unclassified